2001
DOI: 10.1021/la010097i
|View full text |Cite
|
Sign up to set email alerts
|

Negative Differential Resistance in Patterned Electroactive Self-Assembled Monolayers

Abstract: The phenomenon of negative differential resistance (NDR) is potentially very useful in molecular electronics device schemes. Here, it is shown that NDR can be observed in self-assembled monolayers composed of electroactive thiols on gold. Furthermore, these monolayers can be patterned using a scanning probe lithography technique described earlier to form a basis for potential molecular electronic device construction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
132
0
5

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(141 citation statements)
references
References 37 publications
4
132
0
5
Order By: Relevance
“…By designing and positioning the proper molecules in the device the desired functionality is obtained. SAMs have been used as molecular memories [21], molecular wires [22], and have exhibited negative differential resistance [23].…”
Section: A Self-assembled Monolayers (Sams) On Solid Substratesmentioning
confidence: 99%
“…By designing and positioning the proper molecules in the device the desired functionality is obtained. SAMs have been used as molecular memories [21], molecular wires [22], and have exhibited negative differential resistance [23].…”
Section: A Self-assembled Monolayers (Sams) On Solid Substratesmentioning
confidence: 99%
“…These monolayers can be easily oxidized and reduced in solution and are well characterized by electrochemical methods [3], although the mercaptoalkylferrocenes tend to aggregate and form multilayers [4]. Their localized electrical behavior was addressed by scanning probe methods finding a negative differential resistance effect caused by external oxygen, as well as thickness changes upon oxidation/reduction of the ferrocene moiety [5]. To further characterize the influence of the ferrocenes on the charge-transfer behavior of the molecule, it is desirable to manufacture mixed monolayers with isolated mercaptoalkylferrocenes embedded into a topographically well-defined matrix SAM of alkanethiols.…”
Section: Introductionmentioning
confidence: 99%
“…STM and C-AFM, in conjunction with methods including use of Hg-drop electrodes, have been used as promising tools for studying the electrical conductance of molecules along the molecular axis [267,268], crossed wires [269], and break junctions [270,271]. As early as the late 90s, the conductance of single molecules embedded in insulating SAM films was discussed and evaluated by Bumm et al [237] and others [272][273][274][275][276], by use of STM. It was, however, shown that estimation of the electrical conductance of adsorbed molecules by use of STM is quite complicated compared with techniques in which the electrode is directly attached to the molecules [267][268][269][270][271].…”
Section: Self Assembled Monolayersmentioning
confidence: 99%